Effects of Firing Time Variations and Explosive Array Length on Seismic Wave Propagation from Quarry Blasts - Klaus G. Hinzen; Sharon K. Reamer; Brian W. Stump (International Society of Explosives Engineers, 1991)
"This study investigates seismic wave propagation from two production shots in a limestone quarry. Our motivation is to investigate the efficiency of two superpositioning techniques. The production shots consisted of an 18 and 20 hole explosive array detonated in a single row with constant delay times of 32 and 20 ms, respectively. A single shot was fired on a neighboring part of the quarry bench. The experiments were instrumented with 20 three component seismometers (35-120 m range). The computer-controlled electronic firing system resulted in firing time deviations of less than 1.4% of desired fired times. Linear superpositioning with the observed single shot data produces seismograms which adequately reproduce temporal effects of the multiple explosions; however, spatial effects due to the extended source length (68-76 m) are not modeled with this method. Linear superpositioning with individual half-space Green's functions for each explosion in thearray convolved with a calculated Mueller-Murphy source produces seismograms which match the time duration of the observed production shot seismograms and differ in absolute peak amplitude by less than a factor of three. Parameter estimation for the source is taken from chemical explosion study results. The single source model differs in amplitude from the observed single source seismograms by a factor of 2.3."